A critical analysis of the employment tax incentive - Rohhamlal, Natasha (My University, 2018)
The Employment Tax Incentive (‘ETI’) was at the time of introduction in 2013 seen to be a temporary but effective measure to address the high rate of youth unemployment in South Africa. The ETI provides employers with a Pay-As-You-Earn tax credit for those qualifying employees, it employed. The ETI was then seen as one of many incentives to be rolled out which would improve the youth unemployment rate as part of Government’s National Development Plan. This study is a critical analysis of the ETI regime and includes an analysis of certain components of the ETI legislation which could lead to inadvertent negative results. In addition, this report also looks at a scheme created within the industry that makes use of the ETI benefit but does not create employment. Finally, this report concludes on the effectiveness of the ETI in its current form and also provides certain recommendations to the legislature that could make the ETI more effective.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Commerce (specialising in Taxation), Johannesburg, 2018
Keywords: South Africa.--Employment Tax Incentive Act, 2013; Labor laws and legislation--South Africa; Payroll tax--Law and legislation--South Africa